Analisis Kinerja Keuangan pada PT. Perusahaan Gas Negara Tbk Diukur dengan Metode Eva pada Bei - Eni Saputri; Isnaini Harahap; Rahmat Daim Harahap (Jurnal Akuntansi dan Keuangan, 2022)
This study aims to measure and determine the causes of the rise and fall of financial performance when viewed from the value of Economic Value Added (EVA). This research uses descriptive research with a qualitative approach. Technical analysis of the data used is the Economic Value Added method. Data collection techniques are carried out through documentation of the data published by PT. Perusahaan Gas Negara Tbk. The results of this study found that the financial performance of PT. Perusahaan Gas Negara Tbk for five years has decreased every year. This means that the company's financial performance is not good, because the company cannot increase the added value or profits obtained and cannot adjust the needs of the company's investors in that period. The cause of the decline and increase in financial performance when viewed with Economic Value Added (EVA) is because the amount of NOPAT is lower than the capital charge so EVA decreases.